Effects of photovoltaic systems on the behavior of harmonic components in low voltage network - Lipták, Róbert; Bodnár, István (Analecta Technica Szegedinensia, 2023)
Renewable energy sources, especially solar systems, have become increasingly important energy sources in recent times. Connecting large PV systems to utility networks can cause a number of operational problems for distribution networks. The extent of these problems depends directly on the percentage of PV penetration and the geographical location of the installation. Possible problems caused by PV systems: over-voltage, output power fluctuation, harmonic distortion, frequency fluctuation Harmonic distortion is a serious energy quality problem which can occur in photovoltaic systems due to the use of power inverters that convert direct current to alternating current. The resulting harmonics can cause parallel and series resonances, transformer overheating, and protection device malfunctions, which can reduce the reliability of power supply systems.